ANALISIS LAYANAN INFORMASI UNTUK MEMBINA NILAI KARAKTER PADA PESERTA DIDIK KELAS VIII DI SMP - Handayani, Novi Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to describe information services to foster the character of class VIII students in SMP St. Francis Asisi Pontianank. The method used is lecture method, question and answer, discussion, with the form of research analysis. The sample in this research use 49 people. Data technique used is indirect communication technique, data settlement tool used is psychology scale. Data analysis used is descriptive analysis. From the research results, in detail are as follows; 1) informational services to nurture the character of the learners fairly well. These results can be seen from the results. 2) the value of coaching characters in the learner good. These results can be seen from the data if the data for the variable aspects of most of the information services. 3) There is a significant positive relationship between information services to foster middle class VIII St. Francis Pontiac Asisi Pontianak.         Keywords: Information Service, Character Value Building